2006
DOI: 10.1097/01.coc.0000225412.24750.4c
|View full text |Cite
|
Sign up to set email alerts
|

The Role of α-Blockers in the Management of Lower Urinary Tract Symptoms in Prostate Cancer Patients Treated With Radiation Therapy

Abstract: Basic and clinical science studies as well as clinical guidelines relevant for LUTS secondary to RT suggest that the routine use of alpha1-adrenoreceptor antagonists should be considered in patients treated with RT, either prophylactically or at the earliest sign of LUTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 56 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…58 Animal studies have shown that the ventral prostates of rats treated with the α-adrenergic receptor agonist phenylephirine are affected by interstitial fibrosis, inflammation, neoangiogenesis, and de novo synthesis of collagen (suggestive of a desmoplastic reaction). 59 Conversely, other studies have shown that the ventral prostates of adult Wistar rats treated with the α-adrenergic receptor antagonist doxazosin contain increased levels of collagen and collagen fibrils compared with untreated controls.…”
Section: Therapeutic Targeting Of Fibrosismentioning
confidence: 99%
“…58 Animal studies have shown that the ventral prostates of rats treated with the α-adrenergic receptor agonist phenylephirine are affected by interstitial fibrosis, inflammation, neoangiogenesis, and de novo synthesis of collagen (suggestive of a desmoplastic reaction). 59 Conversely, other studies have shown that the ventral prostates of adult Wistar rats treated with the α-adrenergic receptor antagonist doxazosin contain increased levels of collagen and collagen fibrils compared with untreated controls.…”
Section: Therapeutic Targeting Of Fibrosismentioning
confidence: 99%
“…Radiation therapy decreases gland size and may relieve symptoms but can also exacerbate obstructive and irritative symptoms [8,9]. α-Blockers, 5α-reductase inhibitors and anticholinergics are used in the management of LUTS in patients with benign prostatic conditions [10] and also less commonly to alleviate symptoms in patients with PrCa undergoing radiotherapy [11]. …”
Section: Introductionmentioning
confidence: 99%
“…Also, we were unable to control for alpha-blocker usage. Our use of patient-subjective IPSS warranted addressing the potential influence of pretreatment alpha-blocker therapy, given that alpha-blocker therapy does not affect prostate volume and is a routine consideration during radiotherapy, 26 28 but investigating alpha-blocker effects was not a primary aim in this study. Therefore, an inherent analytic weakness is our lack of differentiation between types of pretreatment alpha-blocking medication, ie, prophylactic, symptomatic, or chronic.…”
Section: Discussionmentioning
confidence: 99%